Malaria in a tertiary health care facility of Central India with special reference to severe vivax: implications for malaria control. (1st September 2013) - Jain, Vidhan; Agrawal, Avyact; Singh, Neeru
Abstract : Plasmodium vivax is now recognized as a cause of severe and fatal infection in many parts of the world. This prospective observational study was undertaken in a tertiary health setting to understand the spectrum of the disease burden and associated complications due to P. vivax malaria in central India. A malaria clinic under Regional Medical Research Centre for Tribals is operational at Netaji Subhash Chandra Bose Medical College and Hospital, Jabalpur in central India, where all fever cases and cases with history of fever were referred for screening of malaria parasite by microscopy and rapid diagnostic test kits. Confirmation of all the cases was done by PCR targeting 18s ribosomal RNA gene of the parasite to exclude mixed infection with P. falciparum . Severe vivax malaria was found in 22 (11·1%) out of 198 vivax patients. Cerebral malaria, seizures, severe malaria anaemia, and respiratory distress each were observed in 32% subjects. Multi-organ dysfunction syndrome was common (36%). Mortality was recorded in two patients and neurological sequelae were also observed in two patients at the time of discharge. This is the first report from Central India where P. vivax has been shown to be associated with severe signs of malaria. Severe vivax malaria is a relatively new clinical entity and further studies from different parts of the world are needed to understand clinical spectrum and burden of P. vivax not only for successful treatment, but also for designing and developing effective malaria control measures.